1996
DOI: 10.1177/00220345960750081401
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-term Wear of Conventional and Resin-modified Glass Ionomers

Abstract: Various studies have shown that glass ionomers are susceptible to brittle fracture and acid conditions and that they undergo long-term changes in their mechanical properties. Little information is available on how brittleness, acid susceptibility, and long-term changes are reflected in the wear characteristics of glass ionomers. The purpose of this study was to evaluate long-term changes in conventional glass ionomers, metal-reinforced glass ionomers (including a cermet), and (light-curing) resinmodified glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 30 publications
7
73
0
1
Order By: Relevance
“…This may be due to the low resistance to early wear, and the formation of glass ionomer matrix (20). Therefore, part of the glass ionomer remained adhered to the tooth structures, while part was broken at the interface GIC-tooth.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the low resistance to early wear, and the formation of glass ionomer matrix (20). Therefore, part of the glass ionomer remained adhered to the tooth structures, while part was broken at the interface GIC-tooth.…”
Section: Discussionmentioning
confidence: 99%
“…At extremely high volume fractions, there may be an element of increased brittleness, leading to more rapid crack propagation. Studies showed that the resin-modified glass ionomers exhibit poor wear characteristics, with conventional glass ionomers being subject to high early wear, apparently as a result of subsurface fatigue phenomena (de Gee et al, 1996).…”
Section: (V) Applications Of Fatigue Data Analysis (Va) Life Predictionmentioning
confidence: 99%
“…22 Furthermore, loss of restoration may also occur due to contamination at any step of the bonding process that can adversely impact the longevity of the restoration and hamper its clinical success. 23 Furthermore, 4 restorations in Group A and 3 in Group B were partially lost at 15 months which was replaced by re-application of giomer. A careful examination of these restorations revealed that these restorations were replaced due to chipping of the materials.…”
Section: Discussionmentioning
confidence: 99%